Bangladesh - Civic Engagement in Procurement Reform : Policy Note - World Bank (Washington, DC, 2013)
This policy note has two objectives in the context of Bangladesh: (i) identify possible modalities for increasing social awareness among the general public to demand best value for money in the use of public funds and, through this, for promoting a general acceptance of social accountability as a legitimate form of engagement between the public sector, the citizenry, and the private sector; and (ii) provide guidance on (a) how to engage government officials and the contracting community in adopting a culture shift towards more transparent practices and (b) how to communicate to the public the importance and benefits of adopting behavior well suited in facilitating greater efficiency and effectiveness of public procurement. Both these objectives can contribute to the emergence/ engagement of highly visible and vocal civil society organizations in the monitoring of procurement process as well as outcomes, particularly those interest in fighting corruption. This policy note discusses the need to induce as well as propose a possible approach to stimulating behavioral change among all stakeholders to the public procurement system in Bangladesh (government, civil society, and private sector) that brings acceptance of the idea or concept of social accountability as a legitimate form of engagement.